Journal of Biosecurity, Biosafety and Biodefense Law (De Gruyter, 2011)
The Journal of Biosecurity, Biosafety and Biodefense Law (JBBBL) offers both a legal and scientific perspective on current issues concerning bioterrorism, public health and safety, and national security. JBBBL is aware that bioterrorism related issues are global problems. Our goal is to develop a unique international community of legal scholars, scientists and policy experts who will address current issues in these fields.